Information retrieval tools as predictors for information resources utilization in academic Libraries in Nigeria - David-West, Boma Torukwein (International Journal of Knowledge Content Development & Technology, 2020)
Abstract The study examined information retrieval tools as predictors for information resources utilization, four research questions and four hypotheses were made to guide the study.The descriptive survey was adopted for the study.Random sampling technique was used to select sample 394 from population of 557 academic staff registered in the University of Port Harcourt library.Questionnaire was adopted as data collection instrument titled information retrieval as predictors for information resources utilization (IRPIRQ). Data were analyzed using both simple and multiple regression while analysis of variance (ANOVA) associate with regression was used for testing the hypotheses at 0.05 alpha level.,The study revealed that there is a significant relationship between information retrieval tools and information resources utilization. Further findings revealed that academic staff made use of search engine more often than the OPAC and online database.It was recommended among others that a new library software be installed in place of KOHA for wider connectivity. and adequate distribution of software that will aid usage of the online database and OPAC. URL: http://ijkcdt.net/xml/24904/24904.pdf